ANALYSIS OF VULNERABILITY AND RISK OF QUEBRADA GRANDE OF SAN ANTONIO DEL TEQUENDAMA-CUNDINAMARCA (2023)
Quebrada Grande is a tributary of the Bogotá River of great importance within the municipality of San Antonio del Tequendama. Therefore an analysis of the risks, threats and vulnerabilities that ranged from its source in the Peñas Blancas reserve to its